2020
DOI: 10.3390/nu12010157
|View full text |Cite
|
Sign up to set email alerts
|

Ginger on Human Health: A Comprehensive Systematic Review of 109 Randomized Controlled Trials

Abstract: Clinical applications of ginger with an expectation of clinical benefits are receiving significant attention. This systematic review aims to provide a comprehensive discussion in terms of the clinical effects of ginger in all reported areas. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guideline, randomized controlled trials on the effects of ginger were investigated. Accordingly, 109 eligible papers were fully extracted in terms of study design, population characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
127
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 86 publications
1
127
0
2
Order By: Relevance
“…Cinnamon supplementation in other clinical trials was associated with gastrointestinal disorders and allergic reactions, which were self-limiting in the majority of cases [ 31 ]. Heartburn, nausea, diarrhea, abdominal pain, bloating, gas, and epigastric distress were reported in clinical trials using ginger supplementation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cinnamon supplementation in other clinical trials was associated with gastrointestinal disorders and allergic reactions, which were self-limiting in the majority of cases [ 31 ]. Heartburn, nausea, diarrhea, abdominal pain, bloating, gas, and epigastric distress were reported in clinical trials using ginger supplementation [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adverse events reported in clinical trials are generally mild and often similar to the placebo group (Table 1). A very recent systematic review, which retrieved 109 clinical trials, reported that 70 studies provided information about adverse effects, most of which were not considered to be severely harmful to the participants (Anh et al, 2020).…”
Section: Safetymentioning
confidence: 99%
“…Ginger is mainly promoted and used as an antiemetic, and many clinical trials have been carried out to support this use in cancer patients, pregnant women, and in motion sickness. A recent systematic review of the literature allowed to observe that the majority of ginger clinical trials are related to its antiemetic actions (47/109), followed by the analgesic antiinflammatory (24/109), and metabolic (16/109) actions (Anh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Catechins) Antioxidant Anti-inflammatory Antiviral Cell protection against free radicals and unscheduled apoptosis. Evidence shows cocoa's protective action against some influenza strains [ 164 , 165 ] Garlic ( Allium sativum L.) Allicin and thiosulfinates Antibiotic Antifungal Antivirals Anti-inflammatory Protective action against the flu virus (in addition to other viruses such as cytomegalovirus and herpes) [ 166 – 168 ] Ginger ( Zingiber officinale Roscoe ) Gingerols Antioxidant Anti-inflammatory In addition to the anti-inflammatory property, there is evidence that indicates an improvement in respiratory function, shorter duration of mechanical ventilation and shorter intensive care unit hospitalization in patients with Acute Respiratory Distress Syndrome [ 169 , 170 ] Grapes and grapes-derived products Resveratrol Antioxidant Anti-inflammatory In addition to the already known properties of resveratrol in chronic non-communicable diseases, evidence shows immunomodulatory functions and infectious disease prevention. The protective effect in vitro studies with coronavirus (less cell death, less cytotoxicity and greater cell viability after treatment with resveratrol).…”
Section: Bioactive Compoundsmentioning
confidence: 99%